2008
DOI: 10.1063/1.3000478
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, electrical and magnetic properties of Ce-doped BiFeO3 thin films

Abstract: Bi 1 − x Ce x FeO 3 (x=0, 0.05, 0.1, 0.15, and 0.20) (BCFO) thin films were deposited on Pt/TiN/Si3N4/Si and fluorine-doped SnO2 glass substrates by sol-gel technique, respectively. The effect of Ce doping on the microstructure, electrical and magnetic properties of BCFO films was studied. Compared to counterparts of BiFeO3 (BFO) film, the fitted Bi 4f7/2, Bi 4f5/2, Fe 2p3/2, Fe 2p1/2, and O 1s peaks for Bi0.8Ce0.2FeO3 film shift toward higher binding energy regions by amounts of 0.33, 0.29, 0.43, 0.58, and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(42 citation statements)
references
References 42 publications
8
34
0
Order By: Relevance
“…The enhancement of remnant polarization has been reported in several papers [22][23][24][25][26][27][28][29]. The remnant polarization of La-doped BiFeO 3 thin films was 90 lC cm -2 , compared to undoped one, which was 70 lC cm -2 [26].…”
Section: Ferroelectric Propertiesmentioning
confidence: 79%
See 2 more Smart Citations
“…The enhancement of remnant polarization has been reported in several papers [22][23][24][25][26][27][28][29]. The remnant polarization of La-doped BiFeO 3 thin films was 90 lC cm -2 , compared to undoped one, which was 70 lC cm -2 [26].…”
Section: Ferroelectric Propertiesmentioning
confidence: 79%
“…The remnant polarization of La-doped BiFeO 3 thin films was 90 lC cm -2 , compared to undoped one, which was 70 lC cm -2 [26]. Polarization-electric field hysteresis loops measurement [22] revealed that the value of the remnant polarization BiFeO 3 and Bi 0.8 Ce 0.2 FeO 3 films increases in electric field. According to Quan et al [22], the values of this parameter for the BiFeO 3 and Bi 0.8 Ce 0.2 FeO 3 thin films under an applied electric field of 621 kV cm -1 were 1.57 and 3.12 lC cm -2 , respectively.…”
Section: Ferroelectric Propertiesmentioning
confidence: 96%
See 1 more Smart Citation
“…The epitaxial BFO thin films exhibited large remanent polarization P r (50-150 μC cm −2 ) and large coercive field E c (100-250 kV cm −1 ) [1,11]. Substitutions of partial Bi 3+ at A-sites with Pr 4+ , Ce 3+ , Er 4+ , and Ba 2+ ions have been proved to be a good way to improve the magnetic properties of BFO films [12][13][14][15][16][17][18]. Among them, Ba 2+ ions are shown to be the best substitution for enhancing saturation magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate Ce cations might be used to substitute for A site Bi 3+ in the BiFeO 3 matrix and Ce cations could stabilize oxygen octahedron that helps decrease Bi volatilization and improve the crystallization. 25,26 Moreover, doping at the Fe site with aliovalent atoms, such as Mn, is found to be advantageous in reducing leakage current and improving both electrical and magnetic properties of BiFeO 3 films. 27,28 The substitution of Mn ions is expected to affect the number of oxygen vacancies as well as the chemical states of Fe ions.…”
Section: Introductionmentioning
confidence: 99%